Carrilho, Ernestina, Alexandra Fiéis, Maria Lobo & Sandra Pereira (eds.), Romance Languages and Linguistic Theory 10: Selected papers from ‘Going Romance’ 28, [Romance Languages and Linguistic Theory 10]. Amsterdam/Philadelphia: John Benjamins, 2018. - Corr, Alice (IBERIA: An International Journal of Theoretical Linguistics, 2018)
Review of Carrilho, Ernestina, Alexandra Fiéis, Maria Lobo & Sandra Pereira (eds.), Romance Languages and Linguistic Theory 10: Selected papers from ‘Going Romance’ 28, Lisbon [Romance Languages and Linguistic Theory 10]. Amsterdam/Philadelphia: John Benjamins, 2016. 330 pp.